Superior surface hardening by cyclic-phase-change-diffusion (CPCD): Supersaturation of hard boride in titanium subsurface layer. (November 2016) - Sarma, B.; Chandran, K.S. Ravi
Abstract: This research demonstrates a novel concept of surface hardening, termed "cyclic-phase-change-diffusion (CPCD), " where cyclic phase transitions were induced at the surface by thermal cycling across the phase transition temperature along with diffusion of surface hardening atoms. Specifically, boron was diffused through the surface of titanium during thermal cycling across the α-β phase transition temperature. The CPCD method is shown to result in an unusually deeper ( 125 μm) and richer boride layer, on titanium, compared that obtained by isothermal diffusion either at the equivalent temperature or at a higher temperature. This concept is quite promising for superior surface hardening of titanium and its alloys. Graphical abstract: